2015
DOI: 10.1016/j.ijsu.2015.06.074
|View full text |Cite
|
Sign up to set email alerts
|

Absorbable bioprosthesis for the treatment of bile duct injury in an experimental model

Abstract: The bioprosthesis served as scaffolding for tissue regeneration. There was no postoperative complication at 6 months follow-up. This bioprosthesis could be used to replace the bile duct in cancer or bile duct injury. The bioprosthesis may allow different modeling depending on the type of bile duct injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…In our model, we found that it was possible to replace only a selected portion of the liver with the xenogenic CMS, reducing clinical and surgical complications, compared with the decellularization process. The animal model was successfully reproducible, confirming that the CMS can be tailored to the size and form required, as previously reported ( 13 ). Regarding biocompatibility and the regeneration process, we selected PH as it is the most common model for regeneration.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our model, we found that it was possible to replace only a selected portion of the liver with the xenogenic CMS, reducing clinical and surgical complications, compared with the decellularization process. The animal model was successfully reproducible, confirming that the CMS can be tailored to the size and form required, as previously reported ( 13 ). Regarding biocompatibility and the regeneration process, we selected PH as it is the most common model for regeneration.…”
Section: Discussionsupporting
confidence: 85%
“…Bile duct injury was induced in a porcine model, followed by choledochectomy and CMS implantation. Biosorption of the material occurred 6 months after the surgical procedure, with no tissue alteration or evidence of stenosis ( 13 ). In addition, we recently reported the implantation of CMS in the livers of rats.…”
Section: Introductionmentioning
confidence: 99%
“…The development and use of tubular scaffolding whether biological or synthetic, represents an area of opportunity as a viable therapeutic alternative for this type of injury. (Pérez et al, 2013;Montalvo-Javé et al, 2015) Pérez et al (2013) built three-dimensional collagen tubes coated with 2% agarose hydrogel. This material was implanted in 40 experimental animals substituting the native bile duct.…”
Section: Biomaterials Implant Overviewmentioning
confidence: 99%
“…The use of decellularized matrices for bile duct repair has focused on employing tubular tissues distinct from bile duct, such as ureter [ 9 ]. Furthermore, the animal sources employed in decellularization vary greatly and lack human anatomy resemblance [ 9 , 10 , 11 , 12 ]. Therefore, using porcine decellularized extrahepatic bile duct scaffolds may tackle the disadvantages before-mentioned, due to the anatomical similarities between species.…”
Section: Introductionmentioning
confidence: 99%